Pyogenic granuloma associated with periodontal abscess and bone loss - A rare case report - Bhrugesh J Panseriya; Shital Hungund (Wolters Kluwer Medknow Publications, 2011)
A diverse group of the pathologic process can produce the enlargement of soft tissues in the oral cavity and often present a diagnostic challenge. This soft tissue enlargement may represent a variation of the normal anatomic structure, inflammatory reaction, cyst, neoplasm, and developmental anomalies. A group of reactive hyperplasias, which develop in response to chronic recurring tissue injury that stimulates an excessive tissue repair response. The pyogenic granuloma (PG) is a reactive enlargement that is an inflammatory response to local irritation such as calculus, a fractured tooth, rough dental restoration, and foreign materials or hormonal (pregnancy tumor) and rarely associated with bone loss. This paper presents a rare case of PG associated with periodontal abscess and bone loss in a 30-year-old male.